Carpal Tunnel Syndrome Pathophysiology: Role of Subsynovial Connective Tissue - Werthel, Jean-David R.; Zhao, Chunfeng; An, Kai-Nan; Amadio, Peter C. (Journal of Wrist Surgery, 2014)
Carpal tunnel syndrome (CTS) is a very common pathology. Its most common diagnosis is idiopathic. Although it is accepted that chronic increase in pressure within the carpal tunnel is responsible for median nerve neuropathy, the exact pathophysiology leading to this pressure increase remains unknown. All the histological studies of the carpal tunnel in the CTS find a noninflammatory thickening of the subsynovial connective tissue (SSCT), which seems to be a characteristic of this pathology. Numerous animal models have been developed to recreate CTS in vivo to develop and improve preventive strategies and effective conservative treatments by a better understanding of its pathophysiology. The creation of a shear injury of the SSCT in a rabbit model induced similar modifications to what is observed in CTS, suggesting that this could be a pathway leading to idiopathic CTS.
Keywords: carpal tunnel; subsynovial connective tissue; animal models